The effect of kangaroo mother care on weight gain in infants with low birth weight - Lintungsari, Ursula Swastika; Lepita, Lepita; Sari, Utin Siti Candra (ELECTRON (Journal of Science and Technology), 2024)
Low Birth Weight (LBW) infants are newborns weighing less than 2,500 grams. Infants aged one month or younger, especially those with LBW, face high health risks that can be fatal without proper care. Kangaroo Mother Care (KMC) is a method of caring for low birth weight or premature infants through direct skin-to-skin contact between the mother and the baby, which has been proven to facilitate breastfeeding and improve infant outcomes. This study aimed to analyze the effectiveness of the KMC method on weight gain among low birth weight infants at Dr. Soedarso Regional General Hospital, Pontianak, West Kalimantan. A quasi-experimental design with a pretest-posttest approach was used, involving 40 mothers as respondents. Data were analyzed using a One-Way ANOVA test. The results showed that KMC performed for four hours resulted in a mean weight gain difference of 471.5 grams, with a statistically significant effect (F = 10.476; p = 0.000). It can be concluded that the Kangaroo Mother Care method is effective in increasing the body weight of low birth weight infants, with the four-hour duration providing the most optimal results.